Envisaging a ‘smoke-free’ world: An exploratory study of Philip Morris International’s strategic positioning in Australia - Wolf, Katharina; Cirillo Woodman, Danielle; Maycock, Bruce; McCausland, Kahlia (2020)
The World Health Organization (WHO) has declared tobacco smoking a global health epidemic, citing 8 million deaths and an economic cost of around 1.4 trillion USD per year. Under a UN mandate a global voluntary target was established in 2013 to reduce the prevalence of tobacco use, with varying success rates across the globe to date. While there has been a gradual reduction in combustible cigarette smoking rates across the developed world (Drope et al., 2018), there has been a sharp increase in the popularity and usage of electronic cigarettes (e-cigarettes) since their introduction in 2003 (Drope et al., 2018; McCausland, Maycock, Leaver, & Jancey, 2019). The tobacco and vaping industries claim that e-cigarettes products are less harmful than traditional cigarettes as they are non-combustible, and produce an aerosol with fewer toxic elements like tar and carbon monoxide (Hajek, Etter, Benowitz, Eissenberg, & McRobbie, 2014; Simonavicius, McNeill, Shahab, & Brose, 2018). Indeed, as combustible cigarettes become less socially acceptable and demand decreases, the tobacco industry has increasingly positioned e-cigarettes as part of the solution to reach the WHO’s smoking reduction targets. E-cigarette uptake in Australia remains comparatively low to that in other developed nations (Greenhalgh & Scollo, 2018). This is likely the result of current laws preventing the sale of e-cigarettes containing nicotine in all Australian states and territories due to nicotine’s classification as a schedule 7 ‘dangerous poison’ (Greenhalgh, Grace, & Scollo, 2019). However, given the success of targeted public health policies, such as the Australian Federal laws banning smoking in enclosed places, increased taxing of tobacco products and the introduction of the world’s first plain packaging laws in 2012 (Scollo & Greenhalgh, 2018), the tobacco industry’s lobbying efforts have shifted to establish e-cigarettes as a socially acceptable alternative. Philip Morris International (PMI) controls the main share of the global tobacco market and is the second biggest tobacco company in Australia (Freeman, Winstanley, & Bayly, 2019). This study used framing theory to critically analyse corporate communication materials from PMI to identify the prevailing themes used to challenge Australia’s existing e-cigarette regulations and garner public support for broader access to nicotine containing e-cigarette products. The inclusion criteria for data collection were materials published between January 2018 and July 2019 relating to PMI’s e-cigarettes, heat-not-burn (HNB) products or ‘smokefree’ transformation. 1,534 items were identified for thematic analysis, covering posts across PMI’s social media accounts, media releases, news articles, reports, whitepapers, communication to public health professionals, as well as submissions to two government enquiries. Seven themes and 19 sub-themes emerged from this data. Tobacco Harm Reduction emerged as the dominant theme from the thematic analysis, with references to harm reduction woven through most materials. Other key frames include; PMI as a good corporate citizen, advocating on behalf of smokers, lobbying governments, science and innovation, improved public health outcomes and justifying the presence of nicotine in their Reduced-Risk Products (RRPs). The authors argue that the frame of science and innovation is crucial in understanding how PMI attempts to build trust among consumers; investors and shareholders; lobby government; and divide the public health sector. PMI use extensive research and development expenditure to add credibility to harm reduction claims of their RRPs and to consequently legitimise their claimed position of authority. Indeed, PMI appears to position themselves as the ‘white knight’ of society, campaigning to improve health outcomes, where the public health sector has apparently failed.